KEMAL’S INFIDELITY AND ITS INFLUENTIAL FACTOR IN ORHAN PAMUK’S THE MUSEUM OF INNOCENCE - AYU SETYA RAHAYU (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
KEMAL’S INFIDELITY AND ITS INFLUENTIAL FACTOR IN ORHAN PAMUK’S THE MUSEUM OF INNOCENCE Ayu Setya Rahayu English Department, Language and Arts Faculty, State University of Surabaya cosmeticmiracle@yahoo.com Drs. Much. Khoiri M.Si. English Department, Language and Arts Faculty, State University of Surabaya much_choiri@yahoo.com Abstract Infidelity is defined as unfaithfulness of being unreliable or being attracted to someone other than one relationship partner. There are two types of infidelity, emotional and sexual infidelity. What constitutes an act of infidelity varies within cultures and depends on the type of relationship that exists between people.This study is aimed to present infidelity as experinced by Kemal as the main character in Orhan Pamuk’s The Museum of Innocence, and to reveal the most influential factor of his infidelity.The study uses descriptive qualitative research with psychoanalitic approach. The object of the study is The Museum of Innocence by Orhan Pamuk, published in New York by vintage books in 2009. The data are in the form of quotation, fragments, and dialogues or monologues that indicated the thoughts and action concerning form of infidelity, and also its most influential factor. The data is analyzed by applying the theory of infidelity by Dirgosta and Barta, and also the most influential factor of it. This study also uses the theory of love and will by Rollo May to reveal his influential factor that lead to his infidelity based on the concept above and the quotation depicted in the novel.The result of this study shows thatKemal, the main character of this novel, commits both sexual and emotional infidelity. Initially, he becomes emotionally connected with someone outside of his relationship named Fusun. One way of looking at emotional infidelity is, that it is very dangerous, because it is not only takes away time and energy from his relationship, but it lead him to sexual infidelity and to the end of his engagement. Andthe main factors of Kemal’s infidelity represented from this novel is he falls in love with someone else named Fusun. Actually, this novel is story of love of Kemal and Fusun, then his feeling of love that prompted him to take an action in certain direction which can realize his purpose of love. Because in love, there is definitely a will to unite with beloved people, then it gives rise a boost in his heart to betray his fiancee. Keywords: Infdelity, love, will, novel Abstrak Perselingkuhan didefinisikan sebagai ketidaksetiaan, diandalkan atau tertarik pada orang lain di luar dari pasangannya . Ada dua jenis perselingkuhan , perselingkuhan emosional dan seksual . Yang merupakan suatu tindakan perselingkuhan bervariasi dalam budaya dan tergantung pada jenis hubungan yang ada antara manusia. Penelitian ini bertujuan untuk menyajikan perselingkuhan yang di alami oleh Kemal sebagai sebagai tokoh utama dalam novel berjudul The Museum of Innocence karya Orhan Pamuk, dan untuk mengungkap faktor yang paling berpengaruh dalam perselingkuhannya.Penelitian ini menggunakan penelitian deskriptif kualitatif dengan pendekatan psikoanalisis . Objek penelitiaan ini adalah novel The Museum of Innocence karya Orhan Pamuk , yang diterbitkan di New York oleh vintage books tahun 2009 . Data tersebutdi peroleh dalam bentuk kutipan , fragmen , dan dialog atau monolog yang menunjukkan pemikiran dan tindakan mengenai bentuk perselingkuhan Kemal dan juga faktor yang paling berpengaruh. Data dianalisis dengan menerapkan teori perselingkuhan oleh Dirgosta dan Barta untuk mengungkapkan refleksi penggambaran perselingkuhan Kemal dan juga faktor yang paling berpengaruh. Penelitian ini juga menggunakan teori cinta dan keinginan oleh Rollo May untuk mengungkapkan faktor paling berpengaruh yang mengarah pada perselingkuhan yang didasarkan pada konsep di atas dan kutipan yang digambarkan dalam novel. Penelitian ini menunjukkan bahwa Kemal , tokoh utama dalam novel ini , melakukan perselingkuhan baik seksual mapun emosional . Awalnya , ia menjadi terhubung secara dengan seseorang di luar hubungannya, bernama Fusun . Salah satu cara untuk melihat perselingkuhan emosional adalah , bahwa sangat berbahaya , karena tidak hanya menghilangkan waktu dan energi dari hubungannya sebelumnya , namun membawanya ke perselingkuhan seksual, hingga merusak pertunangannya dengan Sibel. Dan faktor utama perselingkuhan oleh Kemal yang tergambar dalam novel ini adalah ia jatuh cinta dengan orang lain bernama Fusun . Sebenarnya , novel ini adalah kisah cinta Kemal dan Fusun , maka perasaannya cinta yang mendorongnya untuk mengambil tindakan dalam arah tertentu yang dapat mewujudkan tujuan cintanya . Karena di dalam cinta , pasti ada keinginan untuk bersatu dengan orang-orang yang di cintainya, kemudian memberikan dorongan dalam hatinya untuk mengkhianati tunangannya . Kata kunci: Infidelity, love, will, novel Introduction Within the context of intimate relationships, infidelity has been defined as a partner’s violation of norms pertaining to the level of emotional or physical intimacy in which people engaged in outside the relationship (Drigotas & Barta, 2001:45). In the currentera,many strange phenomena appear and done by society. One of the interesting behavior in humansare donetoday is infidelity and that is very oftenaround environment. Not only household commit infidelity, but also in interpersonal relationship. The phenomenon of infidelity is dominant on the socioeconomic statu sof middle to top, especially in big cities. Moreover, the problem of infidelity is often atrigger forvarious cases of divorce or even murder. There are two kinds of infidelity that occurs in today's modern society, the emotional and sexual infidelity.Emotional infidelity in channeling emotional feeling for someone outside the relationship or marriage, whilesexual infidelity isi having sexual intercourse outside of relationship or marriage.The case of emotional infidelity begin when two beings of different sex, begin exchange of information, and the feelings that it was actually supposed to be feel just exclusive for partner. And started to be worse when there is no excitement and keep the distance with ypartner and began to yearn to talk to someone else, rather than the one romantic partners. The climax it will past the limit and begin to emerge the real problem in the relationship that shouldn’t happen, that’s secrets and lies. And when the lie begins,it will difficult to stop. Then, sexual infidelity is just waiting for the right moment. Talking about infidelity, nobody can remove it from the word "love", because if the lovethat isbuilt with the previous couple is strong and sturdy, then the affair could have been avoided. Love is a natural thingin human life. Love is a basic human emotion, but understanding how and why it happens is not necessarily easy. In fact, for a long time, many people suggested that love was simply something that they couldn't understand. Accoding to Erich Fromm, to love somebody is not just a strong feeling, but it is a decision, it is a judgement, and it is a promise,if love were only a feeling there would be no basis for the promise to love each other forever (McGee G. Mark, 1980:208).It means that if the love is just relying on feeling, without the underlying on bond and the sacred promise, as well as the commitment to be together forever, then that love won’tlast long. Psychologist Rollo May proposed that romantic love is made up of four elements: sex, eros, philia, and agape.In conclusion, adult personal relationships containing four forms of love, this relationship based on the sexual satisfaction, a desire for eternal unification and non egoistic concern for the welfare of others. But unfortunately, this kind of authentic love quite difficult to accomplish. At the same time, love hint of tenderness, passion, commitment, and devote themselves to the beloved personal interests, from there, love gives rise to will, the will is an impulse that comes from love, where lover have a will to unite with people they love (May, 1969: 146). In this case, if the love for partneris not strong enough to keep the relationship in order to survive and also the lack of commitment and promise, then sometime there will arise a feeling of love to others, and if the love is greater than the old partner, then the infidelity could happen. In literature like novel, many of whichraised issue of infidelity, where in novel, is related to the human's emotion and expression of feeling, Including ideas, motivation, and describe it by using language. Novel also has people or characters with their own personalities that can represent and act to carry issues that occur in the society. Morover, the dispositive of characters is described in outline only and the events described, contains a mental conflict, which resulted in a change of fortunes. A novel TheMuseum of Innocence by Orhan Pamuk has many sources in culture, love, social, combined into a variety of events and actions. The Museum of Innocence by Orhan Pamuk also depicts infidelity between a rich man and a poor shop girl, in the background of the Turkish city which at that time was experiencing modernization. These issues of infidelity in the background of love willbe discussed in more interesting and more complex from a variety of perspectives in one character. Orhan Pamuk was born in Istanbul in 1952 and grew up in a large family similar to those which he describes in his novels Cevdet Bey and His Sons and The Black Book, in the wealthy westernised district of Nisantasi. As he writes in his autobiographical book Istanbul, from his childhood until the age of 22 he devoted himself largely to painting and dreamed of becoming an artist. After graduating from the secular American Robert College in Istanbul, he studied architecture at Istanbul Technical University for three years, but abandoned the course when he gave up his ambition to become an architect and artist. He went on to graduate in journalism from Istanbul University, but never worked as a journalist. At the age of 23 Pamuk decided to become a novelist, and giving up everythingnelsenretreatednintonhisnflatnandnbeganntonwrite. His first novel Cevdet Bey and His Sons was published seven years later in 1982. The novel is the story of three generations of a wealthy Istanbul family living in Nisantasi, Pamuk's own home district. The novel was awarded both the Orhan Kemal and Milliyet literary prizes. The following year Pamuk published his novel The Silent House, which in French translation won the 1991 Prix de la découverte européene. The White Castle(1985) about the frictions and friendship between a Venetian slave and an Ottoman scholar was published in English and many other languages from 1990 onwards, bringing Pamuk his first international fame. The same year Pamuk went to America, where he was a visiting scholar at Columbia University in New York from 1985 to 1988. It was there that he wrote most of his novel The Black Book, in which the streets, past, chemistry and texture of Istanbul are described through the story of a lawyer seeking his missing wife. This novel was published in Turkey in 1990, and the French translation won the Prix France Culture. The Black Book enlarged Pamuk's fame both in Turkey and internationally as an author at once popular and experimental, and able to write about past and present with the same intensity. In 1991 Pamuk's daughter Rüya was born. That year saw the production of a film Hidden Face, whose script by Pamuk was based on a one-page story in The Black Book. His novel The New Life, about young university students influenced by a mysterious book, was published in Turkey in 1994 and became one of the most widely read books in Turkish literature. My Name Is Red, about Ottoman and Persian artists and their ways of seeing and portraying the non-western world, told through a love story and family story, was published in 1998. This novel won the French Prix du meilleur livre étranger, the Italian Grinzane Cavour (2002) and the International IMPAC Dublin literary award (2003). From the mid-1990s Pamuk took a critical stance towards the Turkish state in articles about human rights and freedom of thought, although he took little interest in politics. Snow, which he describes as “my first and last political novel” was published in 2002. In this book set in the small city of Kars in northeastern Turkey he experimented with a new type of “political novel”, telling the story of violence and tension between political Islamists, soldiers, secularists, and Kurdish and Turkish nationalists. Snow was selected as one of the best 100 books of 2004 by The New York Times. In 1999 a selection of his articles on literature and culture written for newspapers and magazines in Turkey and abroad, together with a selection of writings from his private notebooks, was published under the title Other Colours. Pamuk's most recent book, Istanbul, is a poetical work that is hard to classify, combining the author's early memoirs up to the age of 22, and an essay about the city of Istanbul, illustrated with photographs from his own album, and pictures by western painters and Turkish photographers. Orhan Pamuk’s books have been translated into 46 languages, including Georgian, Malayan, Czech, Danish, Japanese, Catalan, as well as English, German and French. Pamuk has been awarded The Peace Prize, considered the most prestigious award in Germany in the field of culture, in 2005. In the same year, Snowreceived the Le Prix Médicis étranger, the award for the best foreign novel in France. Again in 2005, Pamuk was honoured with the Richarda Huck Prize, awarded every three years since 1978 to personalities who “think independently and act bravely.” In the same year, he was named among world’s 100 intellectuals by Prospectmagazine. In 2006, TIME magazine chose him as one of the 100 most influential persons of the world. In September 2006, he won the Le Prix Méditerranée étranger for his novel Snow. Pamuk is an honorary member of the American Academy of Arts and Letters, and holds an honorary doctorate from Tilburg University. He is an honorary member of the American Academy of Arts and Letters as well as the Chiese Academy for Social Sciences. Pamuk gives lectures once a year in Columbia University. Lastly, he received the 2006 Nobel Prize for Literature, becoming the second youngest person to receive the award in its history. Apart from three years in New York, Orhan Pamuk has spent all his life in the same streets and district of Istanbul, and he now lives in the building where he was raised. Pamuk has been writing novels for 30 yearsnandnneverndonenanynothernjobnexceptnwriting.(http://www.orhanpamuk.net/biography.aspx) The Museum of Innocence is the latest Orhan Pamuk’s novel, published on August, 2009.Pamuk has been working on the novel for many years and it has been hinted by himself in many interviews during this period. The story, which takes place in Istanbul between 1975 and today, is about obsessive love and the great questionof what is love. This colorful and fabulous novel will not only challenge the reader’s thoughts about love, but also those about marriage, sex, passion, family, friendship, and happiness. The story begin with the apparent narrator named Kemal who is engaged to be married to Sibel. Kemal is a rich man when he by chance encounters a long-lost relation, Fusun, a young shopgirl whose beauty stirs all the passion denied him in a society where sex outside marriage is taboo. But Kemal, a young man with high passion has several times having sex with Sibel, and of course it is also more likely to do so with Fusun. Kemalwho really falls in love with Fusun,goes ahead anyway with his long-planned engagement to perfect partner Sibel, then Fusun disappears. Kemal finally breaks off with Sibel, finds Fusun, waits eight years for her to dump her husband (by going to her family’s home some four times a week). In relationship, there will be many problems. The union of two different people, usually can cause contention and eventually lead to big problems. Feelings of love, affection, understanding, and accepting shortcomings of couple, is the very need in a relationship. Because according to psychologist Erich Fromm in his book The art of loving (2006:99) love is an essential of human need. That is, if theneed love is not fullfilled it will cause the problems.In this novel, Kemal who had been engaged to a woman with equal social class with him, women withwell education and from a wealthy family, it seems perfect to be his life partner. Kemal eventually leaveshis fiancée in order to pursue his dream to be unite with Fusun.The infidelity issues in the novel has the most significant cause,Kemal lack of affection to his fiancee, so that makes him fall in love with another woman. This novel begin at Istanbul in 1975. Kemal is a rich and engaged man But when Kemal encounters Füsun, a poor beautiful shopgirl and a distant relation, he becomes enthralled. And once they violate the code of virginity, when sex before married considerd as taboo at that time. The firsttime hemetwithFusunwaswhenhe boughtjennycolon bag tohis fiancee, sibel, an upper-class beautiful girl. The city of Intanbul is captured by pamuk with a romantic touch, sturdy apartments of the rich man, once supported. The lovers met in Merhamet Apartments, in a flat abandoned by his mother. He dated his first secret meeting with Fusun to the spring of 1975. At that time, Pamuk initially planned Kemal to marry Sibel, a fashionable young woman with enlightened views of life, she goes without limits enlightened with Kemal. Love becomes the main motive, when someone can destroy virginity code. Fusun ends their relationship when she learns of Kemal’s engagement with Sibel. But Kemal cannot forget her. It will take Kemal almost a year to find her again, a year of driving through every neighbourhood of the enormous city, months of heavy drinking in which he loses all interest in Sibel, even after they move in together. Sibel hopes to save him from what seems an inexplicable sadness, and learning the truth enrages her. To her, Füsun is just "a common shopgirl", a slut, even though they have each only slept with one man. Both sexual and emotional infidelity bound this novel. How kemal lie and keep his secret relationship to sibel, while he loves someone else and having sexual intercourse with Fusun. Psychologist Rollo May defines love into various types, such as sex, eros, philia, and agape. Sex is defined in category where someone loves another person just because of an underlying sexual appetite. Eros is defined as a lover which includes not only sexual intimacy, but also the feeling of love, attention, care so as to make the relationship last. Philia is defined as a sincere friendship, while gape is defined as selfless feeling or don’t expecting reward (Jess Feist and Gregory J. Feist, 2009:58-59). In the case of Kemal in this novel, his love for Sibel does not meet all of four elements above, thus making their relationship is not too strong to survive. Then he finds Fusun, and feel the perfect love. In analyzing Kemal’s infidelity and the most influential factor, it is used some related concept and one theory. In this thesis, the problem statement is divided into two. The first problem statement deals with how Kemal’s infidelityreflected in this novel. While the second problem deals with the most influential factor of Kemal’s infidelity. Those problems can be analysed by using the psychological approach as the base of the guide and theory. The first statement is how Kemal’s infidelity reflected in The Museum of Innocence. This statement will use the concept of infidelity by American psycologyst, Dirgostra and Barta. This concept is united and merged with the bases of marital or extramarital relationship. There are two kinds of infidelity in this concept. The writer will analyses which kind of infidelity that Kemal uses through the quotations and monologues. Then the second statement is what is the most influential factor of Kemal’s infidelity. This statement will also apply the concept of infidelity factor. Actually, the are a lot of infidelity factos, but the writer only use one factor that tha most represent based on quotation in this novel. The factor is love.So, ithe writer will use the theory of love and will that become the most influential factor of Kemal’s infidelity. This concept is developed by existential psychologyst, Rollo May. It is about the unity between love and will, this circles of love and will is however affected to his infidelity. Methods Research methodolgy that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research..The data obtained to answer research question study. This study uses novel of Orhan Pamuk entitled The Museum of Innocence that published in 2009 as the data source of this study. The datas are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicate and represent aspect of infidelity and love and will which is experienced by the main character. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. Some steps of how the data is analyzed will be described as follows: Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are two classifications in this study. They are infidelity and The main factor that lead to his infidelity. Describing Kemal’s infidelity which is stated from the quotations or statements by using theory of infidelity to be applied to the data. Describing the most influential factor of Kemal’s infidelity which is stated from the quotations or statements by using theory of love and will to be applied to the data. RESULT How is the students’ writing ability of SMP Muhammadiyah 5 in writing descriptive text after they being taugh by picture puzzle. Infidelity, is the main topic that will be analyzed. Many couples are under the misconception that infidelity only occurs when a man and a woman have sex together. Yet, there are other forms of infidelity such as emotional infidelity. Emotional infidelity may take on different forms, but in general it is the act of forming an emotional connection with someone outside of one’s formal relationship. Kemal Brasmaci, the main character of the novel, born as a wealthy and well eucated instanbul family in Nisantasi. His fascinating live, ranging from being a socialite among A class people, and he prefers to live as a modern Turkish, in which at the time, Turkey was undergoing modernization with the influence of European culture. 30-year-old Kemal Basmaci, works as a bussinessman and lives in Merhamet Apartment which will be a silent witness to his secret love adventure with his distance relation, Fusun. Initially, Kemal is set to be engaged to a well educated and high socety girl named Sibel. Kemal first meetsFusun when he bought a Jenny Colon bag to Sibel in Sazalize boutique where Fusun works in. When he step up in Sazalize boutique, Kemal looks like very attentive to every detail in Fusun’s clothes and shoes, her yellow skirt, her empty shoe over her long bare legs, her long till Dexterous fingers. Kemal begins to admire Fusun’s beauty. Knowing that, because it was less than 10 years they had not met. There was a silence. I looked again into one of the pockets she had just pointed to inside the bag. Her beauty, or her skirt, which was in fact too short, or something else together, had unsettled me, and I couldn’t act naturally. (Pamuk, 2009:6) Based on quotation above, Kemal gives the impression of a "darting" man by notices detail of what Fusun wear. Her skirts that look very short, her beauty, and anything else that can not be said. Actually, it does not really matter, but there is something rustled in Kemal’s heart. It became the beginning of Kemal’s interest feeling to Fusun. Moreover, Kemal also admittes that he can’t act naturally when dealing with Fusun, he feels uneasy, but rather, look awkward in front of the opposite sex, there is definitely something special, something that raises passions and encouragement in his heart, even if it happens on the first time he meet. In this case, Kemal commits emotional infidelity by having eventual emotional connection, or a feeling of interest with someone other than one his romantic partner. Beside perform emotional infidelity, Kemal also perfor sexual infidelity has been defined as behaviour of a sexual nature carried out with someone other than one's primary partner.Usually, cheating involves people meeting face – to - face, and then engaging in physical intimacy. Beside having emotional infidelity with Fususn, he also comitted sexual infidelity, because the emotional affair can lead to phsycal affair. the intimate nature of the communication, plus the emotional investment made by the people involved, places an emotional infidelity become more intimate, and perform sexual intercourse, such as having sex kissing, touching, etc. The verry first page in this novel Tells about Kemal's happiest moment of his life. Having sexual intercourse with Fusun in his appartement. We felt the same coolness rising from the musty mattress on which we were making love, the way children play, happily forgetting everything else.(Pamuk, 2009:1) Based on quoatation above, it is clearly mentioned that Kemal comittes sexual infidelity by having sexual contact with Fusun, a woman other than his one romantic partner. In the firs page of this novel, Kemal explained clearly how and the steps of having sex with Fusun, and describes the atmosphere when they were in apartment when doing so. Because having sex is actually become a necessity. They look really enjoyed with the secret relationship, the way the kids played, happy to forget everything else seemed to describe what they both feel at that moment, as if they feel in pleasure without limits and make them forget themselves, forget about all the obstacles and problems that never happened, that there was only pleasure at that time. The second analysis is about The most influential factor of Kemal’s infidelity. In this novel, Kemal Brasmaci a perfect gentleman, well educated, came from a wealthy, and respectable family in the city, is set to be married to perfect Sibel, who comes from an equal family as him. Many people assume if they are a perfect match. Kemal actually love Sibel, the woman who would soon be engaged to him. They both underwent a romantic date, having a harmonious family, came into exclusive places, even they both also have made love, although in that era, having sex outside of marriage is considered as taboo. Psychologist Rollo May argues that love is a pleasure, love is a pleasure to the presence of someone, as well as a confirmation of the value and development of the beloved person, just like themselves. Love is able to make a big motivation to someone, which raises the desire to realize the dream to be unite with someone they love. While Will of its own, generating an action to self directed, so that certain goals can be achieved. Kemal actually has already realized if what he has done is the most fatal mistake in his life, even he can not imagine how the devastation that can occur, as a result of these actions. But Still his love for Fusun become a big power that able to beat all obstacle. Kemal has been trying to forget Fusun, consider if he never loved Fusun. But, it can be covered by his feelings love that he could never lose, and always encouraged him to betray his old partner. Finally, Kemal continued to repeat the days of their togetherness, having sexual intercourse in his apartement. I am certain that the fire at the heart of my tale is the desire to relive those moment of love, and my attachment to those pleasure. For years, whenever I recalled those moments, seeking to understand the bond I still felt with her, images would from before my eyes, crowding out reason; for example, Fusun would be sitting on my lap, and I would have taken her large left breast into my moth. (Pamuk, 2009:53) From the quotation above, it is illustrated that Kemal feels her turmoil, that grows more fiery, he even wants to revive the her passion of making love with Fusun, because it is considered as a pleasure for him. Kemal is very attached, and no longer awkward in doing his pleasure in his secret relationship with Fusun. His tremendous sex desire to make love with Fusun, bring it into delusion when they're together. Kemal always be remembered while they are making love, for example when Fusun sits on his lap, and he holds the Fusun’s left breast, then puts into his mouth. The thing that Kemal does based on description above is sexual infidelity, because he was having sex with a woman other than his partner. Kemal pleasure in making love with Fusun, is the Will of Kemal who loves Fusun. That is, the Kemal’s impulse to commit sexual infidelity influenced by his love for Fusun. It was proved that Kemal has strong emotional ties to Fusun like people who really love his partner, even for many years, Kemal still remember the time they spent together, which can not be removed from his memory. Conclusions From overalls of this study, can be conclude that Kemal comitts infidelity, by having a relationship with Fusun, and violate her engagement to Sibel. In this novel, Kemal commits two types of infidelity, they are emotional and sexual infidelity. Kemal enjoying passionate sexual intercourse and perform a deep emotional attachment with Fusun. Kemal committs both infidelities at the same time. At first, Kemal perform emotional infidelity with Fusun, starting when he met with Fusun in Sanzalize boutique, where Fusun work, he began to admire Fusun, beauty, watching his every movement, pay attention to her clothes. From there, came a strange feeling inside Kemal’s heart that he had not been aware of. But over time, that feeling grow stronger. Moreover, the two lovers are getting often met. Emotional Infidelity sounds fairly simple, but it is not as simple as that. Precisely emotional infidelity more dangerous than those who experienced only sexual infidelity. Because sometimes emotional infidelity could lead to a more intimate relationship, and over time will be difficultto integral, as experinced by kemal. As already described above, that emotional infidelity can lead to sexual infidelity, because the people who are already emotionally attached, will also certainly have the desire to have sexual intercourse.In this novel, Kemal also perform sexual activities that are engaged in with someone other than one 's partner. Activities that constitute sexual infidelity include all forms of physical intimacy, from kissing to sexual intercourse. Its pretty clearly described through the evidents in this novel, that Kemal and Fusun often make an appointment to meet at the apartment and Kemal to meet, it is like two people in a drunken romance.It has been shown clearly to the quotation analysis of the first statement problem that Kemal perform his first sexual infidelity, starting by giving a kiss, till make a love. Second conclusion is, actually there must bereasonsbehindKemal’s infidelity. But themost crucial factor that is found based on the novel’s quotation is his love for Fusun since the beginning of his meeting in a boutique. Initially, Kemal did not have any shortage in his relationship with Sibel, his fiancee.He admitts that he loves Sibel. Even though it is not described implicitlythe describtion of his love for Sibel, but it can be inferredeksplicitly that Kemal was not really love Sibel, it is proven when Kemal seems too easy to fall in love with someone else, and since then, his attention on sibel start to reduced, and even when his relationship with Fusun grows further, he decides to break his engagement with Sibel. People who really love their partner sincerely, certainly will not to do so. Love, which is built by Kemal and Fusun is very great anf strong, exceeding Kemal’s love to Sibel, probably thi is because Kemal and Sibel’s relationship came from matchmaking. Kemal who love Fusun, give birth to a Will for betraying his fiancee, Sibel. It means that the Will here, is an impulse to do something, without being influenced by the values ​​of the good or bad.Those impulse can take him into a particular direction in which the desired goal can be realized. People who loves someone, like Kemal, definitely have a desire to be happy with Fusun, or want to united with her, So that it can give rise animpulse in his heart to betray his partner, so he could be much longer having relationship with Fusun, a person he love. Refference Drigotas, S.M., & Barta, W. 2001. The cheating heart:Scientific explorations of infidelity.New York: Guildford Press Feist, Jess and Feist, Gregory J. 2009.Teori Kepribadian:Theory of Personality. Terjemahan Sjahputri Smita Prahita. Jakarta:Salemba Humanika ----------------------------------------. 2009. Theories of Personality. Terjemahan Santoso Yudi. Jakarta:Pustaka Belajar Friedman S., Howard, Miriam W. Schustack.(2006). Kepribadian Teori Klasik dan Riset Modern. Jakarta:Erlangga Fromm, Erich, 2006. The Art of Loving.Seoul:Choun Publishing Co. Glass, S. P., & Wright, T. L. 2004. The relationship of extramarital sex, length of marriage,and sex differences on marital satisfaction and romanticism:Athanasiou's data reanalysed. Journal of Marriage and the Family May, R. 1967. Pshycology and the Human Dillema. Princeton, NJ:Van Nostrand McGee, Mark G. 1980. Introductory Psychology Reader. St. Paul: West Publishin CO. Pamuk, Orhan.2009. The Museum of Innocence. New York: Vintage Internet Source: http://www.orhanpamuk.net/biography.aspx